POLA INTERAKSI USTADZ DAN SANTRI DALAM PEMBELAJARAN ( Studi Kasus di Pondok Pesantren Mambaul Hisan Blitar) - Salamah, Umi; Hidayatulloh, Arif (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2019)
The success of a learning process is very closely related to the process of interaction. In Islamic boarding schools, a religious teacher besides becoming a teacher must become uswah / example in instilling religious values and moral values. In addition, the interaction between the religious teacher and students is expected to provide understanding to students including the ability of cognitive, affective and psychomotor. The purpose of this study is to describe the form of religious teacher and student interaction, the process of interaction between religious teacher and students, and the impact of interaction between religious teacher and students in the cottage. boarding school Mambaul Hisan Blitar. This study uses a qualitative approach to the type of case studies, using data collection techniques of observation, interviews, and documentation. Data analysis in this study uses data condensation, data display, and verification. The results of this study indicate that 1) the interaction between the cleric and the santri consists of three forms, namely one-way interaction, two-way interaction and multi-way interaction. 2) The process of educational interactions occurs in two kinds, namely outside and inside the teaching-learning process. 3) The impact of the interaction that was built between the cleric and the santri was to add insight into the religious scholarship of the santri, making the santri always prioritize aspects of the morality of the mercy, words in kromo, good manners and good social ethics, santri were more responsible and disciplined in carrying out their obligationsKeywords: interaction pattern; learning process